Unbowed : a memoir - Maathai, Wangari Muta (New York : Anchor Books, 2007)
The recipient of the 2004 Nobel Peace Prize describes her life as a feminist, political activist, and environmentalist in Kenya, detailing the 1977 establishment of the Green Belt Movement and her role in the transformation of Kenya's government.
Appendix : Konyeki na ithe, or "Konyeki and his Father"
Includes index.
Keywords: Maathai, Wangari; Green Belt Movement (Society : Kenya); Tree planters (Persons) -- Kenya -- Biography; Women conservationists -- Kenya -- Biography